Isolated zone I vertical sacral fracture: a case report - AlBarazanji, Asim; Moghamis, Isam Sami; Mudawi, Aiman; Ajaj, Abdulla Ahmed; Khan, Munir; Qaimkhani, Saeed Ahmed (International Journal of Research in Orthopaedics, 2025)
Isolated sacral fractures are not common. This is attributed to the lack of segmental motion of the sacral bones, and most sacral fractures are transversely oriented. However, vertically oriented sacral fractures are never isolated and are usually associated with pelvic ring fractures due to the shearing force of the pelvic ring. There are only a few case reports of such injury presented in isolation. We are reporting a case of isolated zone I vertical sacral fracture in a 25-year-old female following a road traffic accident with a lateral compression mechanism of injury. Only a few cases related to isolated sacral fractures have been reported in the literature. To our knowledge, there have only been a few reports of vertical sacral fracture following a lateral compression injury. Complete vertical sacral fracture with significant displacement in isolation is a rare injury, as it is usually associated with pelvic ring injuries. Surgical stabilization is an indication of such injury to restore the stability of the pelvic ring.